Clinical significance of the phenotype of immune cells of the tumor stroma of prostate cancer - P. A. Podlesnaya; O. V. Kovaleva; M. A. Rashidova; D. V. Samoilova; A. A. Petrenko; V. V. Mochalnikova; A. N. Gratchev (Успехи молекулярной онкологии, 2022)
Introduction. Prostate cancer is by far the most frequently diagnosed cancer among the male population and ranks fifth in the world in terms of mortality rates among malignant neoplasms. Today it is known that the tumor microenvironment plays an important role in the pathogenesis of the disease. Abundant data has accumulated indicating that cells of the inflammatory infiltrate of the tumor are involved in the onset, progression and response to treatment in cases of prostate cancer. However, their role in the context of disease progression has not yet been determined. In this work, we studied the phenotype of inflammatory infiltrate of prostate cancer and its association with the clinical and morphological characteristics of patients.The study objective is to determine the features of the inflammatory infiltrate of prostate cancer and its association with the clinical and morphological characteristics of patients with this disease.Materials and methods. The study included tumor samples obtained from 31 patients with prostate cancer. The expression of CD3, CD8, FoxP3, CD68, PU.1, CD204, CD163, IDO1, PD-L1 (programmed death-ligand 1) was assessed by immunohistochemistry. The relationship between markers and clinical and morphological characteristics was assessed using the nonparametric Mann–Whitney test and Fisher’s exact test. Spearman’s rank correlation coefficient was used to analyze the correlations between contents of cells of different phenotypes. Differences were considered statistically significant at p <0.05.Results. This study describes the features of the stroma of prostate cancer. We have shown that an increased content of CD204+ cells is associated with an older age of patients (p = 0.0026), and the number of CD163+ and CD8+ cells with no metastases to regional lymph nodes (p = 0.0067 and p = 0.0069, respectively). It has been shown that PU.1 can be used as a general marker of macrophages. We also found significant correlations between the level of PU.1 and PD-L1 in the stroma (r = 0.421; p = 0.018) and IDO1 in the stroma (r = 0.557; p = 0.001) and in tumor cells (r = 0.393; p = 0.029), CD68 with IDO1 in the stroma (r = 0.535; p = 0.002), CD163 with PD-L1 and IDO1 in the stroma (r = 0.399; p = 0.026 and r = 0.220; p = 0.026, respectively).Conclusion. In this work, the characteristics of the stroma of prostate cancer were investigated. Our data indicate that tumor associated macrophages are the main cells expressing PD-L1 and IDO1 in the tumor stroma in the case of prostate cancer. Increased expression of IDO1 in tumor tissue is associated with the immunosuppressive phenotype of the inflammatory infiltrate. The fact that the number of macrophages directly correlates with the number of T-lymphocytes in the prostate stroma, and the number of M2 macrophages with cytotoxic T-cells indicates the interaction of the mechanisms of innate and acquired immunity during the progression of prostate cancer.